Investigation and analysis of lower extremity arterial disease in hospitalized elderly type 2 diabetic patients - Xiang Lu; Jiao Sun; Jiao-Jiao Bai; Yue Ming; Li-Rong Chen (Elsevier, 2018)
Background: The risk of lower extremity arterial disease (LEAD) is increased in diabetic patients. LEAD in diabetic patients occurs earlier and is often more severe and diffuse; however, it is largely underdiagnosed and untreated. The purposes of this study were to investigate and analyze LEAD situation of hospitalized elderly type 2 diabetic patients. Methods: The ankle-brachial index (ABI) was used to screen LEAD in hospitalized elderly type 2 diabetic patients. The patients were divided into 5 groups based on the screening results: non-LEAD group and LEAD group; the LEAD group was divided into mild stenosis group, moderate stenosis group, and severe stenosis group. Results: The percentage of patients who had LEAD was 43%. Significant difference in age, diabetes duration, peak velocity, microalbuminuria, and vibratory sensory neuropathy was observed between patients with and without LEAD; regression analysis showed that urinary albumin and vibratory sensory neuropathy were independent risk factors for LEAD. Significant difference in age, body mass index (BMI), peak velocity, urinary albumin, and high-density lipoprotein cholesterol (HDL-C) was observed between mild stenosis group, moderate stenosis group, and severe stenosis group; regression analysis showed that urinary albumin, BMI, and HDL-C were independent risk factors for accelerating vascular stenosis. Conclusions: The incidence of LEAD in hospitalized elderly type 2 diabetic patients is high; age, diabetes duration, peak velocity, BMI, urinary microalbumin, vibratory sensory neuropathy, and HDL-C are the major risk factors for LEAD. Active control of risk factors is helpful to reduce or delay LEAD. Keywords: Aged, Ankle-brachial index, Diabetes mellitus, type 2, Diabetic angiopathies, Hospitalized, Lower extremity arterial disease